Evaluation Of The Integrated Teacher Training Program During The Covid-19 Pandemic at The Faculty Of Tarbiyah and Teacher Training IAIN Ambon - Jumaeda, St.; Husein, Saddam (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to find out the level of achievement of the purpose of Integrated Teacher Training (PPKT) activities during the covid-19 Pandemic at the Faculty of Tarbiyah and Teacher Training (FITK) IAIN Ambon. This study uses evaluative research on PPKT program activities at FITK IAIN Ambon, using a goal-oriented evaluation model developed by Ralph Winfred Tyler. Data collection in this study, conducted using observation techniques, interviews, questionnaires, and documentation. The subjects in this study are field Guidance Lecturer, pamong teacher, organizing committee and PPKT students. The results of the study showed that the preparation and orientation carried out by the organizing committee in accordance with the conditions set out in the PPKT guidelines of the Faculty of Tarbiyah and Teacher Training IAIN Ambon were in the good category. Â The implementation of PPKT FITK IAIN Ambon student work program, including the implementation of students before learning practice, learning practice, practice exams, community service based on community learning about covid-19, and PPKT student guidance conducted by field guidance lecturers (DPL) and teachers, as a whole in the category of good. But for the learning practice component is still not maximal, because learning is done online, so that PPKT students at the time of learning practice do not get the experience that should be obtained when meeting directly with students in school.